The clinical features and initial pharmacotherapeutic options of children with Tic disorders - Xiang, Yuxin; Tong, Chang; Sun, Dan; Liu, Zhisheng (Frontiers in Pediatrics, 2025)
PurposeTic disorders (TD) are common childhood neurodevelopmental conditions, characterized by diverse manifestations, leading to misdiagnosis and delayed therapy. Timely identification of TD and access to care can improve clinical outcomes. This retrospective study characterizes clinical features and initial pharmacotherapy in newly diagnosed pediatric TD.MethodThis retrospective cohort study included 805 newly diagnosed pediatric TD patients. Tic severity was assessed using the Yale Global Tic Severity Scale (YGTSS), with patients stratified into mild (YGTSS scores < 25), moderate (25–50), and severe (>50) groups. Chi-square tests/Fisher-exact tests and Wilcoxon rank—sum tests compared group differences in baseline characteristics. Multivariate analyses identified factors associated with tic severity, and logistic regression analyses identified predictors of pharmacotherapy initiation.ResultsIn 805 subjects, 73.43%, 11.18% and 15.39% were classified into provisional tic disorder, chronic tic disorder, and Tourette syndrome (TS). The prevalence of comorbid attention-deficit/hyperactivity disorder (ADHD) was higher in moderate (21.45%) and severe (36.36%) groups than in the mild group (15.60%). The diagnosis of Tourette syndrome (aOR = 1.40, 95% CI: 1.23–160.31), age at onset (aOR = 1.63, 95% CI: 1.22–2.18), and age at diagnosis (aOR = 1.63, 95% CI: 1.22–2.17), comorbid ADHD (aOR = 7.12, 95% CI: 1.39–36.43) were positively associated with greater tic severity. Clonidine patch (CAP) and traditional Chinese medicine (TCM) were the most common choices initial pharmacotherapy in newly diagnosed pediatric TD. Scores of YGTSS, comorbid ADHD predicted treatment initiation.ConclusionsThis study contributed insights into the clinical profiles across tic severity and pharmacotherapeutic approaches in newly diagnosed pediatric TD. The findings highlighted the independent associations between baseline factors and tic severity, as well as the predictors of pharmacotherapy initiation. CAP and TCM served as the most common choices in newly diagnosed pediatric TD.